Problems of linguo-cultural analysis of phraseological units in the French and Uzbek languages - Akhmedovna, Iroda Juraeva; Sodikovna, Gulsara Kurbonova (Linguistics and Culture Review, 2021)
This article is devoted to the study of linguistic and cultural problems of toponymic component phraseologies in French and Uzbek languages. The article pays special attention to the emergence of toponymic component phraseologies on the basis of extralinguistic factors. It examines the national and cultural features of phraseology, their role in enhancing the methodological color of the work of art and the theoretical aspects of the translation of these units, as well as the views of linguists on the linguistic and cultural nature of phraseology. Factors of emergence of toponymic component phraseology in the article 1) phraseology based on socio-historical factors; 2) phraseology, the origin of which is associated with folk art; 3) phraseology related to everyday life, customs and traditions of people; 4) analyzed on the basis of mastered phraseology. Also, a quantitative analysis of the sources of origin of phraseological units with a component of national-cultural toponyms in French and Uzbek languages was conducted. The studied toponymic component phraseologies were studied in their own layer and foreign layer, and their quantitative analysis was carried out. In French and Uzbek, the meaningful objects of phraseological units with a toponymic component are studied separately by linguocultural description.